Serum cystatin C - a new marker of glomerular filtration rate - Hojs, Radovan (Zdravniški vestnik, 2004)
Background. Estimation of the glomerular filtration rate is an essential part of the evaluation of patients with renal disease. A standard for glomerular filtration rate assessment is CrEDTA clearance. Serum creatinine is the most commonly used marker to estimate the glomerular filtration rate, but it is often not enough accurate. Recently serum cystatin C has been proposed as a new endogenous marker of glomerular filtration rate. Patients and methods. A total of 231 patients (100 woman and 131 men), who performed CrEDTA clearance in previous 17 months, were enrolled in our study. In each patient serum creatinine and serum cystatin C were also determined. Average age of our patients was 55 years (from 7 to 85 years). Results. Average CrEDTA clearance was 54.4 ml/min/1.73 m2 (from 2 to 186 ml/min/1.73 m2). Average serum creatinine concentration was 270.2 mol/l (from 64 to 915 mol/l) and average serum cystatin C concentration was 2.53 mg/l (from 0.59 to 6.99 mg/l). The correlations between CrEDTA clearance, serum creatinine and serum cystatin C were statistically significant. The correlation between CrEDTA clearance and serum cystatin C was better than correlation between CrEDTA clearance and serum creatinine. Conclusions. CrEDTA clearance, serum creatinine and serum cystatin C are comparable markers of renal function. Based on our study, serum cystatin C is a more reliable measure of glomerular filtration rate than serum creatinine.
Keywords: Cistatini; Creatinine; Cystatins; Glomerular filtration rate; Glomerulna filtracija; Kidney diseases; Kreatinin; Ledvične bolezni